Fatty acid composition and metabolic pathways in Arbacia dufresnii (Arbaciidae: Arbacioida) gametes: implications of shrimp byproducts in aquaculture feeds - Vera Piombo, Mercedes (2024)
Introduction: Care towards nutrition is essential for the quality of a sustainable aquaculture product. Since the balance in food affects the growth and production of gametes. The circular economy is made possible through the use of discarded materials. Objective: The aim of this research was to study the fatty acid composition and metabolic pathways in the gametes of Arbacia dufresnii, with a focus on the implications of incorporating shrimp byproducts into aquaculture feeds. Methods: Four different treatments were designed to maintain optimal nutritional quality, particularly in lipids and proteins, based on previous studies. The fatty acid profiles of the feeds and gametes were analyzed by using gas-chromatography, and statistical analyses were conducted to determine significant differences. Results: Significant differences were observed in the abundance (%) of omega-3 (ω-3) and omega-6 (ω-6) fatty acids. The (ω-3) metabolic pathway was more pronounced in the gametes of wild animals and those fed with the experimental feeds. In contrast, the (ω-6) metabolic pathway was less relevant in these groups. The (ω-3) /(ω-6) ratio was highest in the gametes of wild animals. Feeds enriched in fatty acids enhanced their bioaccumulation in the gametes reaching higher concentrations than wild animals. The availability of fatty acids in foods allowed their bioaccumulation in gametes, with concentrations equal to or higher than those observed in animals in their natural environment for certain fatty acids. Conclusions: Incorporating shrimp byproducts in aquaculture feeds demonstrated a promising strategy for resource utilization and organic input generation. The fatty acid composition in the gametes of A. dufresnii was influenced by the diet, highlighting the potential of balanced feeds to enhance the bioaccumulation of essential fatty acids. These findings provide valuable insights for the development of sustainable aquaculture practices and the production of nutritionally enriched seafood products.